Exercise and Chronic Diseases: A Scoping Review - Imron, Moh. Ali; Adiatmika, I Putu Gede; Jawi, I Made (Faculty of Medicine, Public Health, and Nursing, 2025)
Background: Regular exercise has been postulated as beneficial to prevent, treat, and manage a chronic disease that nowadays is caused by a sedentary life. However, its prescription and mechanism of how exercise positively affects health conditions is requiring further research. Objective: To investigate the types of regular exercise and exercise prescription and mechanisms in preventing or treating a chronic disease. Methods: This study reviewed articles from ProQuest, Science Direct, Wiley, and PubMed using the terms 'chronic disease', 'exercise', 'physical activity', and 'cytokine'. Results: Forty-six articles were reviewed in this study which originated from different regions spanning Asia, Europe, America, and Africa. The articles were categorized based on sample characteristics, which were; elderly, healthy adults, athletes, mice, and others. Each article describes an aerobic or anaerobic exercise performed under various interventions ranging from low, moderate, to high and comprehensively explains its effect on human biology, including on the body system, tissue adaptation, muscle hypertrophy, and neuroplasticity, by examining its effect on proteins, hormones, enzymes, microRNAs, as well as functional metrics pertaining to physical capacity enhancement. Conclusion: This review concludes that exercise will elicit effects on the immune and metabolic systems of people with chronic disease.